Milk production characteristics and productivity of N'Dama cattle kept under village management in The Gambia - Agyemang, K.; Dwinger, R.H.; Grieve, A.S.; Bah, M.L. (American Dairy Science Association, 1991)
Studies milk production characteristics and productivity of N'dama cattle kept under village conditions as part of an epidemiological study designed to identify production constraints and to develop strategies to improve livestock productivity of farmers with small holdings. Milk and component yields were monitored monthly by measurement of milk extracted for human use (milk offtake) plus that consumed by the calf, estimated from body weight changes. Examines lactation length, milk offtake, fat, protein, calf weaning weight, calving interval.